1983
DOI: 10.1016/0022-0965(83)90015-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective information use and perseveration in the search behavior of infants and young children

Abstract: Two experiments examined the early development of selective information use in search. The first experiment tested 9- and 16-month-olds on a modification of Piaget's Stage IV object permanence task. It examined infants' use of information from previous experiences with an object (prior information) and from the most recent hiding (current information) to locate a hidden object. In the second experiment, 2-, 2 1/2-, and 4-year-old children received these same sources of information along with new forms of prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
5
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 22 publications
3
58
5
1
Order By: Relevance
“…used a similar but more complicated version of the MSMLT, used in our research, to study perseverative errors in 54 children, aged 2 to 3 years, and found perseveration by the age of 2 years on this task. Based on a modification of the Piaget's stage IV object permanence task with three hiding locations, Sophian and Wellman (1983) report perseverative errors in children as young as 16 months of age. However, they were rare and there was also evidence of selectivity at that age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…used a similar but more complicated version of the MSMLT, used in our research, to study perseverative errors in 54 children, aged 2 to 3 years, and found perseveration by the age of 2 years on this task. Based on a modification of the Piaget's stage IV object permanence task with three hiding locations, Sophian and Wellman (1983) report perseverative errors in children as young as 16 months of age. However, they were rare and there was also evidence of selectivity at that age.…”
Section: Discussionmentioning
confidence: 99%
“…Perseverative searching on these tasks has been observed in frontally ablated adult monkeys (Diamond & Goldman-Rakic, 1986) and in normal human infants, of less than 12 months (Diamond, 1990). Other studies, using a variety of more difficult search tasks than used in infants, report improvements of search behavior and flexibility at about 3 years (Sophian & Wellman, 1983;Wellman, Somerville, Revelle, Haake, & Sophian, 1984 The overview of these studies shows that according to the age of the children, different assessment tools (search tasks for younger children and sorting tasks for older children) are used to assess AF, leading to different developmental levels of AF abilities in young children. They generally range from 12 months to 4 years and above.…”
mentioning
confidence: 97%
“…Preschool children make many perseverative errors: inappropriate repetitions responses over a series of questions or problems (Luria, 1959). Children perseverate in tests of rule use, word learning, and naming, and in non-verbal tasks (Gerstadt, Hong, & Diamond, 1994;Johnson, 1994;Sophian & Wellman, 1983;Wertlieb & Rose, 1979). For example, infants tend to search for a toy in the last place they found it, not where it was last hidden (Piaget, 1954).…”
Section: Introductionmentioning
confidence: 99%
“…At the very least, we can conclude that arbitrary pictorial cues are not an automatic aid to retrieval for 2-year-olds, while for older subjects such pictures routinely benefit performance. Sophian and Wellman (1983) examined whether children's prior knowledge base could serve as another potential source of discriminative cues in search. As we indicated in our earlier description of their study, Sophian and Wellman added pictures of different rooms to the front of the boxes on some trials.…”
Section: Memory For Locationmentioning
confidence: 99%
“…Children in this older age range are generally quite good at retrieving objects on search tasks, but when they do make errors, search is directed to that location where an object had been retrieved on the preceding trial more frequently than would be expected by chance. Sophian and Wellman (1983) have carried out an extensive analysis of memory for and reliance upon prior and current information by very young children. They defined memory for current information as the ability to find an object in one location before any other location was used for hiding.…”
Section: Memory For Locationmentioning
confidence: 99%